Linguistics Landscape of Culture Representation at Pandawa Beach Kutuh-Bali - Putri, I Gusti Ayu Vina Widiadnya; Andriyani, Anak Agung Ayu Dian (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to analyze the representation of the outdoor sign from the Mahabharata story on the outdoor sign at Pandawa Beach–Kutuh Bali. Pandawa Beach is one of the new tourism destinations in the Badung district which has good tourism potential. The beauty of the beach was initially hidden than known by the public, it required hard work from all parties. To disseminate information on the naming of the hidden beach in this village, an outdoor sign is shown as a representation of the historical value of the Pandawa Beach tourist attraction. This research is field research with qualitative data analysis to examine the appearance of outdoor signs at Pandawa Mbeach attractions. Kutuh Village's traditional figure is the participant in this study. The method of this research is field research by observation method at Pandawa Beach. The technique of collecting data by checking the list, interview, and documentation of the outdoor sign using a digital camera. The method of analyzing data was the qualitative method which was divided into some techniques such as quantification of qualitative data and subject interpretation data. The representation of the Mahabharata Story in Outdoor Sign at Pandawa Beach was analyzed using the theory of four communicative choices. The results of this study indicate that four communication choices were found in the data, such as Language Choice, Pragmatic Choice, Code Choice, and Audience Choice. Based on the result of analyzing data, it can be found that the cultural representation of the outdoor signs at Pandawa Beach is the story of Mahabharata.